New solutions in the European financial security network (Economic and Political Thought, 2018)
The aim of the article is to present the most important EU activities inthe construction of a European financial safety network, both those alreadyundertaken (including in particular: CRD, CRR and Banking Union) as wellas planned (including changes regarding: capital requirements, large exposures,long-term liquidity, financial leverage, risk assessment, reporting of banksand banks referred to as TBTF. In addition, the article assesses the measurestaken in the field of financial market regulation from the point of view ofthree criteria, i.e. stability of the sector, efficiency of banks’ operations andperception of new requirements by banks.
Keywords: financial security network, EU financial market, EU financial architecture, CRD IV Directive, CRR Regulation, banking union, financial liquidity, MREL, TLAC, LCR, NSFR, IFRS 9, TBTF